2011
DOI: 10.1597/09-051
|View full text |Cite
|
Sign up to set email alerts
|

Some Modifications of the Furlow Palatoplasty in Wide Clefts—A Preliminary Report

Abstract: The Furlow technique as originally described has shortcomings. The authors describe their technique of incorporating the Furlow repair, which enables them to use it as a primary palatoplasty, in a scenario consisting of a large percentage of wide clefts in an older age group, thereby minimizing the fistula rate while increasing palatal length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…1). There were five randomized controlled trials 35,37,42,48,55 and 39 nonrandomized studies, [1][2][3]5,9,13,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[38][39][40][41][43][44][45][46][47][49][50][51][52][53][54]56,57 of which 10 were comparative studies and 29 were noncomparative. The mean Detsky score for the randomized controlled trials was 14, with two studies considered to be of high quality.…”
Section: Study Selection and Assessment Of Methodologic Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…1). There were five randomized controlled trials 35,37,42,48,55 and 39 nonrandomized studies, [1][2][3]5,9,13,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[38][39][40][41][43][44][45][46][47][49][50][51][52][53][54]56,57 of which 10 were comparative studies and 29 were noncomparative. The mean Detsky score for the randomized controlled trials was 14, with two studies considered to be of high quality.…”
Section: Study Selection and Assessment Of Methodologic Qualitymentioning
confidence: 99%
“…The age at which primary repair of the cleft palate was performed varied greatly, from 2 months 5 to 37.2 years. 36 Age at surgery was presented in multiple formats, including age range, mean age, median age, and modal age, and as such no valid comparisons can be made or conclusions drawn about the optimum time of intervention.…”
Section: Data Extractionmentioning
confidence: 99%
“…In the literature, the fistula rate following Furlow palatoplasty ranged from 0.76% to 23.3%. 1,10,[12][13][14][15][16][17][18][19][20] Although the fistula rate for Furlow palatoplasty gradually reduced, its occurrence was higher than that of the von Langenbeck procedures. Brothers et al, 21 reported a fistula rate of 0% in 10 patients with Wardill-Kilner palatoplasties versus 5% in 21 patients with Furlow repairs.…”
Section: Discussionmentioning
confidence: 99%
“…11 Velopharyngeal competence allowing development of normal speech is one of the most critical outcomes in cleft surgery, and the Furlow technique has been associated with some of the lowest rates of persistent velopharyngeal insufficiency following primary repair. [52][53][54][55] Alternative models. Though transgenic models offer significant insight, it is difficult to manipulate the development of these mice in utero.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%